2018
DOI: 10.1007/s11910-018-0855-1
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Apnea Is a Risk Factor for Stroke and Vascular Dementia

Abstract: Sleep apnea syndrome of moderate to severe intensity affects 17% of 50-70-year-old men and 9% of 50-70-year-old women, making SA a notorious and prevalent disorder. SA increases the risk of hypertension, stroke, myocardial infarction, and atrial fibrillation (AF) and is closely linked to vascular dementia. In addition, SA may worsen the neurologic outcome in acute stroke patients and interferes with rehabilitation after stroke. Proper management of SA may decrease the clinical impact of stroke risk factors, im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 79 publications
1
26
0
1
Order By: Relevance
“…[2] The association between oSDB and cardiovascular risk in adults is described in the literature. [3] Cicero et al described that self-reported snoring and sleep apnea were considered main independent predictors associated with higher pulse wave velocity (PWV), the gold standard for measuring arterial stiffness, and that augmentation index (AIx), an indirect index of arterial stiffness and direct left ventricular afterload, was signi cantly higher in snorers with or without apnea than in non-snorers. [4] Thus, oSDB appears to be a modi able risk factor for cardiovascular morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…[2] The association between oSDB and cardiovascular risk in adults is described in the literature. [3] Cicero et al described that self-reported snoring and sleep apnea were considered main independent predictors associated with higher pulse wave velocity (PWV), the gold standard for measuring arterial stiffness, and that augmentation index (AIx), an indirect index of arterial stiffness and direct left ventricular afterload, was signi cantly higher in snorers with or without apnea than in non-snorers. [4] Thus, oSDB appears to be a modi able risk factor for cardiovascular morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…A study (Chang et al ., 2013) focusing on the impact of SA on the risk of developing the two most common forms of dementia, AD and VD, reported that SA could increase the risk of VD (adjust HR: 1.93, 95% CI=1.00–3.77; p <0.005). A recent study (Culebras and Anwar, 2018) further demonstrated that older women (mean age 82.3 years) with moderate to severe obstructive sleep apnea were more likely to develop mild cognitive impairment or VD (adjusted odds ratio [AOR], 1.85; 95% CI=1.11–3.08). Hypoxia is the main feature of SA affecting cognition, and microinfarcts are the major lesions of VD.…”
Section: Impact Of Sleep Disorder As a Risk Factor For Dementia In Mementioning
confidence: 97%
“…Periods of apnea are accompanied by periods of hypoxemia and by brief electroencephalographic and autonomic arousals that lead to a disruption of normal sleep architecture [101]. OSA is associated with several chronic conditions, including depression, hypertension, risk of stroke and myocardial infarction, and cardiac arrhythmia [103][104][105][106][107]. OSA is also associated with vascular dementia and with an earlier onset of mild cognitive impairment and dementia compared with subjects without OSA [108].…”
Section: Sleep Disruption In Age-related Comorbiditiesmentioning
confidence: 99%